Pencegahan Risiko Penularan HIV/AIDS dengan Kampanye “Stop Free Sex” - Viyona Indah Permatasari; Moch Sandika Gustian; Ajeng Renata Tamara; Aris Firdaus; Usman Zakariya; Karin Setyawati (Yayasan Inspirasi El Burhani, 2022)
Introduction: Knowledge about HIV/AIDS among adolescents is very important in forming attitudes towards efforts to prevent HIV/AIDS transmission by avoiding risky behaviors such as free sex among adolescents. Free sexual acts are sexual acts that take place without restrictions, either as a single sexual relationship or with those who have sex without formal marriage according to the law and religion, beliefs of each person. Objective: This research is to shape the knowledge and attitudes of adolescents with targeted coaching Method: The community service participants were attended by all students of class X SMK Miftahussalam as many as 40 people. with the lecture method and question and answer the material provided includes: definition of HIV/AIDS and free sex, causal factors, impacts, and prevention of HIV/AIDS and free sex. Result: The result of this activity at SMK Miftahussalam is the implementation of health education regarding the risk of HIV/AIDS transmission by preventing free sex. Before being given counseling about HIV/AIDS and free sex, there were some students who did not understand the risk of HIV/AIDS transmission and prevention of free sex. However, after being given the material, students could understand what HIV/AIDS is and how to prevent it. Conclussion: The conclusion from community service activities at SMK Miftahusaalam can increase students' knowledge and understanding of the material that has been delivered. This activity is expected to be able to reduce the number of free sex incidents directly, and students can have a high awareness of the risks of HIV/AIDS transmission and prevention of free sex and avoid negative behaviors that damage their morals and reproductive health.